2020
DOI: 10.3389/fphar.2020.01086
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae as Potential Anti-Inflammatory Natural Product Against Human Inflammatory Skin Diseases

Abstract: The skin is the first line of defense against pathogen and other environmental pollutant. The body is constantly exposed to reactive oxygen species (ROS) that stimulates inflammatory process in the skin. Many studies have linked ROS to various inflammatory skin diseases. Patients with skin diseases face various challenges with inefficient and inappropriate treatment in managing skin diseases. Overproduction of ROS in the body will result in oxidative stress which will lead to various cellular damage and alter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 130 publications
0
34
0
1
Order By: Relevance
“…The immunomodulator mechanisms include cytokines, interferons, interleukins, and tumor necrosis factors, secreted primarily by macrophages, lymphocytes, and keratinocytes in the epidermis [ 28 , 44 ]. Additionally, various factors such as uncontrolled responses to pathogens, toxic substances and reactive oxygen species ( ROS )-mediated oxidative stress promote the release of pro-inflammatory mediators [ 28 , 45 ]. Accordingly, immunomodulatory agents are used to inhibit inflammatory responses and fight diseases.…”
Section: Immunomodulatory Activity Of Compounds From Microalgaementioning
confidence: 99%
“…The immunomodulator mechanisms include cytokines, interferons, interleukins, and tumor necrosis factors, secreted primarily by macrophages, lymphocytes, and keratinocytes in the epidermis [ 28 , 44 ]. Additionally, various factors such as uncontrolled responses to pathogens, toxic substances and reactive oxygen species ( ROS )-mediated oxidative stress promote the release of pro-inflammatory mediators [ 28 , 45 ]. Accordingly, immunomodulatory agents are used to inhibit inflammatory responses and fight diseases.…”
Section: Immunomodulatory Activity Of Compounds From Microalgaementioning
confidence: 99%
“… 120 , 121 Microalgae and their extracts contain a variety of bioactive components with anti-inflammatory and antioxidant properties. 122 , 123 For example, a microalgae-based wound dressing was developed to promote wound healing by exploiting its anti-inflammatory, antioxidant, and antimicrobial properties. 124 In the case of chronic wounds, a wound dressing that can fight inflammation, sterilize the wound, and minimize local hypoxia is ideal for promoting wound healing.…”
Section: Chronic Wound Healingmentioning
confidence: 99%
“…water, so it is used as an important biomarker to indirectly show oxidative damage to tissues [34]. Clinical and experimental animal studies of AD using AST as treatment have reported significant anti-inflammatory effects [16][17][18][19][20] and balanced Th1 cells and Th2 cells [28].…”
Section: Effect Of Ast Treatment On Gpx-1 Ho-1 Activitymentioning
confidence: 99%
“…A study has reported that AST inhibits intracellular oxidation produced by various ROS, and reduces neurotoxicity induced by hydrogen peroxide (H2O2) or serum deprivation [15]. AST has also been reported to improve AD and contact dermatitis by controlling inflammatory cytokines and inflammatory mechanisms [16][17][18]. Anti-inflammatory effects of AST [19] and liposomal AST [13] in PA-induced animal models of AD have been reported.…”
Section: Introductionmentioning
confidence: 99%